Imaging in the Causes of Secondary Hypertension: Unveiling the Hidden Culprits - Periaswamy, Gopinath; Christopher, Navya; Arunachalam, Venkatesh Kasi; Mangalakumar, V.; Pulappadi, Vishnu Prasad; Mahadevan, Gowtham Sembagoundenvalasu; R., Sriman; R., Rupa; Mehta, Pankaj; Cherian, Mathew (Indographics, 2024)
Secondary hypertension refers to the cases of hypertension having a specific underlying etiology. Secondary hypertension can be further divided to endocrine or nonendocrine causes. Radiologists must accurately identify the secondary causes of hypertension, as many of them can be treated, and treatment can result in improved symptoms or resolution of hypertension. Secondary hypertension requires a thorough imaging investigation using ultrasound, Doppler ultrasound, computed tomography angiography, magnetic resonance imaging, scintigraphy, and other imaging techniques to identify the underlying cause for optimal management.
Keywords: secondary hypertension; endocrinological causes; nonendocrinological causes